FACTORS THAT AFFECT COMMUNITY PARTICIPATION IN THE IMPLEMENTATION OF THE COMPLETE SYSTEMATIC LAND REGISTRATION PROGRAM (PTSL) AT THE PEKANBARU CITY LAND AGENCY OFFICE - Ardi Wahyudi; Rodi Wahyudi (Indonesian Journal of Social Sciences, Policy and Politics, 2026)
The Systematic Land Registration Program (PTSL) is a government initiative aimed at providing legal certainty regarding land ownership for the public. However, in Pekanbaru City, community participation in this program remains relatively low. This research aims to identify the factors that influence both the success and hindrances of community participation in the implementation of the PTSL program at the Pekanbaru Land Office. This study employs a descriptive qualitative method with a field research approach. Data were collected through interviews, observation, and documentation. Informants consisted of land office staff and community members who had participated in or were currently participating in the PTSL program. Data analysis was conducted in three stages: data reduction, data display, and conclusion drawing. The results of the study indicate that community participation is influenced by effective two-way communication, ease of access to information and services, direct involvement in the measurement process, and community-based outreach. However, several obstacles were also identified, including a lack of adequate socialization, financial constraints, the absence of landowners during verification, and suboptimal coordination at the neighborhood level. Therefore, improving communication strategies, ensuring transparency in procedures and costs, and strengthening the role of local community leaders are essential to increasing the effectiveness of the PTSL program.